1991
DOI: 10.1016/0270-9139(91)90114-b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon-γ on hepatitis B viral antigen expression in primary hepatocyte culture

Abstract: Interferon-alpha has been shown recently to selectively enhance hepatocyte expression of HBsAg/pre-S2 in chronic hepatitis B virus infection in a way that may enhance immune recognition. To determine the effect of interferon-gamma on hepatitis B virus antigen expression, hepatocytes isolated from patients with chronic hepatitis B virus infection were incubated in the absence or presence of interferon-gamma and viral antigen expression was assessed by both radioimmunoassay and immunocytochemistry using appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
2
6
1
Order By: Relevance
“…In accord with our findings, they also ob-ments. Although we do not fully understand the reasons for the discrepancies between these findings and those reported here and by Lau et al [1991], several factors may contribute. Among the obvious ones are different viruses (DHBV versus HBV), different host cell lines (Huh 7 versus HepGB), and different IFN preparations.…”
Section: And Reports Of Marginal Successcontrasting
confidence: 93%
See 1 more Smart Citation
“…In accord with our findings, they also ob-ments. Although we do not fully understand the reasons for the discrepancies between these findings and those reported here and by Lau et al [1991], several factors may contribute. Among the obvious ones are different viruses (DHBV versus HBV), different host cell lines (Huh 7 versus HepGB), and different IFN preparations.…”
Section: And Reports Of Marginal Successcontrasting
confidence: 93%
“…Other investigators have examined the effect of IFN-y on HBV expression in alternate systems. Lau et al [1991], using radioimmunoassay and immunocytochemistry on primary hepatocytes isolated from carriers of HBV, found that recombinant IFN-y had a significant inhibitory effect on hepatocyte expression of all intracellular hepatitis B virus antigens. These findings are consistent with our results, and indicate that our findings are likely to be relevant to human HBV infection.…”
Section: And Reports Of Marginal Successmentioning
confidence: 99%
“…The viability of the isolated hepatocytes assessed in parallel by trypan blue dye exclusion and by plastic adherence and eosin staining after 16-h culture was >75%. This result was comparable to the numbers of viable cells observed after short-term culture using similar assays in previous studies [24,25].…”
Section: Hepatocyte Isolationsupporting
confidence: 90%
“…4,5 In hepatitis B, IFN-␣-2b works by inhibiting viral RNA pregenomic packaging into core particles and by enhancing the expression of HBsAg on hepatocytes. 6,7 Many randomized, controlled trials involving Asian, European, and North American subjects have demonstrated that IFN-␣-2b suppresses replication of HBV. [8][9][10][11][12] The efficacy of IFN-␣-2b therapy is evidenced by loss of HBeAg and HBV DNA, which occurs in up to 30-40% of patients 1 year after the start of treatment.…”
Section: Efficacymentioning
confidence: 99%